Lateral osteoperiosteal flap versus lateral pedicle flap in the treatment of class III gingival recession: A single-center, open-label trial - Yarabham Chakravarthy; Rampalli Viswa Chandra; Aileni Amarender Reddy; Gollapalle Prabhandh Reddy (Wolters Kluwer Medknow Publications, 2020)
Aims: The aim of this study was to compare outcomes of lateral osteoperiosteal flap (OPF) and lateral pedicle flap (LPF) in the treatment of Miller's Class III gingival recession. Materials and Methods: Twenty-two anterior maxillary and mandibular sites from 16 participants requiring mucogingival surgery for Miller's Class III gingival recession were included in the study. Eleven sites each were assigned to two groups. OPF: sites treated with lateral OPF and LPF: sites treated with LPF. Recession depth (RD) and bone level (BL) were the primary outcome variables, and probing pocket depth, clinical attachment level (CAL), and keratinized tissue width (KTW) were the secondary variables. All the variables were recorded at baseline (on the day of surgery), 3 months, and 6 months postsurgery. Results: OPF and LPF resulted in similar reduction in RD at the end of the study period (P ≤ 0.001). There was no statistically significant difference in RD between OPF and LPF at 6 months (P = 0.862). OPF-treated sites showed greater gain in BL at 3 months (P = 0.0004) and 6 months (P = 0.0002). No significant differences were seen between OPF and LPF in measures of PD, CAL, and KTW. Conclusion: Data from this 6-month trial seem to suggest that OPF can be used as an alternative procedure for treating Miller's class III recessions with adjacent edentulous sites or wide interproximal spaces. Long-term effects of OPF on the stability of root coverage outcomes are an exciting direction for future research.